Free Nutritious Meals Program Budget and Investor Trust: A Comparative International Study - Tarada Berlian Megananda; Joval Ifghaniyafi Farras (CV Putra Publisher, 2026)
The Free Nutritious Meals Program (Makan Bergizi Gratis/MBG) is among the largest social spending programs in Indonesia's fiscal history, with a 2026 budget ceiling of IDR 268 trillion down from an initial plan of IDR 335 trillion reaching more than 63 million beneficiaries. This study compares the design and GDP-to-budget ratio of MBG with comparable programs in Brazil, India, the United States, Sweden, and Finland, and examines its relationship with investor trust in Indonesia. A descriptive-comparative method based on document analysis of official government reports, international institutional databases, and indexed academic literature was employed. Budget-to-GDP ratios were calculated by the author using official budget figures and World Bank GDP data. Results show that MBG's budget share (estimated at 1.1–1.4% of GDP) far exceeds Brazil's PNAE, India's PM Poshan, and the United States' NSLP (each below 0.1% of GDP). Fitch and Moody's revised Indonesia's outlook to negative over fiscal deficit concerns, while S&P maintained a stable outlook, citing the MBG budget reduction favorably. The study concludes that MBG carries a dual signal: short-term fiscal risk alongside potential long-term human-capital investment value, whose sustainability depends on fiscal policy credibility and program governance.